Fine mapping and resequencing of the PARK16 locus in Parkinson’s disease - Pihlstrøm, Lasse; Rengmark, Aina; Bjørnarå, Kari Anne; Dizdar, Nil; Fardell, Camilla; Forsgren, Lars; Holmberg, Björn; Larsen, Jan Petter; Linder, Jan; Nissbrandt, Hans; Tysnes, Ole-Bjørn; Dietrichs, Espen; et al. (Journal of human genetics, 2015)
The PARK16 locus, spanning five genes on chromosome 1, was among the first genetic regions to show genome-wide association in Parkinson's disease (PD). Subsequent investigations have found variability in PARK16 top-hits and association patterns across populations, and the implicated genes and mechanisms are currently unclear. In the present study, we aimed to explore the contribution of PARK16 variability to PD risk in a Scandinavian population. We genotyped 17 single-nucleotide polymorphisms in a case-control sample set of 2570 individuals from Norway and Sweden to fine map the locus. Targeted resequencing of the full coding regions of SLC45A3, NUCKS1, RAB7L1, SLC41A1 and PM20D1 was performed in DNA pools from a subset of 387 patient samples. We find evidence for an association with PD for rs1775143 as well as a haplotype located around the 5' region of RAB7L1, implicating variants which are not in high linkage disequilibrium with the strongest signal from a recent large meta-analysis in Caucasians. We also provide suggestive support for epistasis between RAB7L1 and LRRK2 as previously hypothesized by others. Comparing our results with previous work, allelic heterogeneity at PARK16 appears likely, and further studies are warranted to disentangle the complex patterns of association and pinpoint the functionally relevant variants.